Koordinasi SPPG Sekolah dalam Program Makan Siang Bergizi Gratis (MBG) di Indonesia: Studi Kasus di Bojonegoro, Jawa Timur - Dwi Prasetyo; Oni Dwi Arianto; Ade Firmannandya; Teguh Dwi Putranto (Research and Development Agency Ministry of Home Affairs, 2026)
This study examines coordination between schools and the Nutrition Food Production Center (SPPG) in implementing Indonesia’s Free Nutritious Meal Program (MBG) in Bojonegoro Regency, East Java, across schools with diverse operational capacities. This study uses integrated qualitative methods by highlighting governance processes—role allocation, communication flows, decision-making, and reporting—rather than impact indicators. Data were generated through purposive focus group discussions with school principals, teacher MBG coordinators, SPPG managers and operational staff, and school committee representatives or parents, and triangulated with relevant program documents. Transcripts were analyzed thematically using iterative coding. Findings show coordination is mainly operational and weakly institutionalized: schools act as passive recipients, while SPPG controls menu selection, production, and logistics, yielding asymmetric, largely one way information exchange. Communication and problem reporting rely on informal messaging and brief delivery-time interactions, with limited documentation, unclear pathways, and inconsistent feedback. These governance gaps contribute to recurring delivery delays, unannounced menu changes, inadequate accommodation for dietary restrictions, and increased administrative workload for schools. They also intensify parental concerns regarding food quality and safety and influence student acceptance, thereby undermining program legitimacy. The study concludes that implementation quality depends on strengthening local coordination capacity through regular coordination forums, standardized reporting and feedback protocols, clearer role and accountability structures, and ongoing technical support aligning centralized standards with context-sensitive adaptation. Institutionalizing coordination would enable the school SPPG network to transition from reactive delivery to continuous improvement, supporting transparent learning, effective risk management, and sustained community buy-in over time.